2009
DOI: 10.1158/0008-5472.can-08-4471
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Human and Rat Uterine Leiomyomata: Identification of a Dysregulated Mammalian Target of Rapamycin Pathway

Abstract: Uterine leiomyomata, or fibroids, are benign tumors of the uterine myometrium that significantly affect up to 30% of reproductive-age women. Despite being the primary cause of hysterectomy in the United States, accounting for up to 200,000 procedures annually, the etiology of leiomyoma remains largely unknown. As a basis for understanding leiomyoma pathogenesis and identifying targets for pharmacotherapy, we conducted transcriptional profiling of leiomyoma and unaffected myometrium from humans and Eker rats, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
71
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 37 publications
4
71
0
2
Order By: Relevance
“…In addition, they found that E 2 treatment increases PTEN in leiomyoma, but not in myometrial cells. Finally, Crabtree and colleagues (94) found upregulated mTOR pathways in leiomyoma, both in human and in the Eker rat animal model. These findings suggest that aberrant PI3K/Akt/mTOR signaling plays a role in leiomyoma pathobiology.…”
Section: Pi3k/akt/mtor Pathwaymentioning
confidence: 97%
“…In addition, they found that E 2 treatment increases PTEN in leiomyoma, but not in myometrial cells. Finally, Crabtree and colleagues (94) found upregulated mTOR pathways in leiomyoma, both in human and in the Eker rat animal model. These findings suggest that aberrant PI3K/Akt/mTOR signaling plays a role in leiomyoma pathobiology.…”
Section: Pi3k/akt/mtor Pathwaymentioning
confidence: 97%
“…107 Like the proliferative smooth muscle cells of LAM lesions, these lines are Tsc2-null and have constitutively active mTORC1 signaling. 108 More importantly, these lines express estrogen and progesterone receptors, and retain their hormone responsiveness. 109,110 Isogenic ELT3 cell lines, T3 and V3, reexpressing Tsc2 or vector control, respectively, have also been generated.…”
Section: Cells Derived From Tsc-null Tumorsmentioning
confidence: 99%
“…Transcriptional profiling of leiomyomas from humans and rats has revealed an up-regulation of mRNA levels of some components in the mTOR pathway compared with normal myometrium. In addition, inhibition of the mTOR pathway by rapamycin analogue WAY-129327 reduces leiomyoma incidence in female Eker rats (9).…”
mentioning
confidence: 99%